Teachers' technology professional development: a Malaysia perspective - Md Khambari, Mas Nida; Wong, Su Luan; Mohd Ayub, Ahmad Fauzi; Moses, Priscilla (Faculty of Educational Studies, Universiti Putra Malaysia, 2010)
This paper centers on the impact of laptop use on the professional development of teachers. Three hundred and eighty six secondary school teachers from 28 selected schools participated in the survey. These teachers were currently teaching Science and Mathematics, and were provided laptop as part of the Teaching and Learning of Science and Mathematics in English, or better known by its Malay acronym PPSMI programme. Teachers’ professional development was measured in three dimensions: teaching learning, administrative practice and use of resources. The analysis revealed that the use of laptop has a moderate impact on the overall teachers’ professional development.